Analisis Kemampuan Pemahaman Matematis Siswa Kelas IX Pada Materi Bangun Ruang - Tommy Tanu Wijaya; Neng Suci Septiani Dewi; Indah Retta Fauziah; M Afrilianto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
The focus in this study is aims to determine the effect of Auditory Intellectually Repetition (AIR) with Problem Based Learning on the ability of mathematical understanding. This study was designed qualitative descriptive method. The instrument essay is the ability of mathematical understanding about geometry. Based on the results and discussion, the effect of Auditory Intellectually Repetition (AIR) with Problem Based Learning on the ability of mathematical understanding ability of mathematical understanding is good with the average of percentage is 70%.Â